Functional development of the circadian clock in the Zebrafish pineal gland - Ben-Moshe Livne, Zohar; Foulkes, Nicholas S.; Gothilf, Yoav (BioMed research international, 2014)
The zebrafish constitutes a powerful model organism with unique advantages for investigating the vertebrate circadian timing system and its regulation by light. In particular, the remarkably early and rapid development of the zebrafish circadian system has facilitated exploring the factors that control the onset of circadian clock function during embryogenesis. Here, we review our understanding of the molecular basis underlying functional development of the central clock in the zebrafish pineal gland. Furthermore, we examine how the directly light-entrainable clocks in zebrafish cell lines have facilitated unravelling the general mechanisms underlying light-induced clock gene expression. Finally, we summarize how analysis of the light-induced transcriptome and miRNome of the zebrafish pineal gland has provided insight into the regulation of the circadian system by light, including the involvement of microRNAs in shaping the kinetics of light- and clock-regulated mRNA expression. The relative contributions of the pineal gland central clock and the distributed peripheral oscillators to the synchronization of circadian rhythms at the whole animal level are a crucial question that still remains to be elucidated in the zebrafish model.
Gesehen am 10.08.2017